Effectiveness of Entrepreneurship Development Programs in Ghanaian Polytechnics - Adjimah, Paul Harrison; Perry, Akli Lawrence (International Review of Management and Marketing, 2013)
This paper examines the effectiveness of entrepreneurship development programs (EDP) of Ghanaian Polytechnics in achieving some objectives. Using a case study methodology the research tracked the entrepreneurship intentions and entrepreneurial tendencies of some Ho Polytechnic students at different stages of their studies over three years. The analysis revealed a very high increase in interest in business proprietorship after the EDP but showed quite a weak link between the programs and most of the entrepreneurial tendencies. The study also noted that the proportion of students who intend to move from school directly into business, though rising after the programs, remained very low.The study finally concluded that the gap between the high level of interest and the willingness to move directly from school into business is a strong case for more policy efforts to initiate programs and projects which can trigger graduates to undertake entrepreneurial activities. Keywords: effectiveness; entrepreneurship intentions; tendencies; entrepreneurship development programs JEL Classifications: I 13; L27